2017
DOI: 10.1161/strokeaha.117.018974
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Natural History of Superficial Siderosis

Abstract: Background and Purpose Superficial siderosis (SS) is characterized by hemosiderin deposition in the superficial layers of the central nervous system and can be seen during post-mortem examination or with iron-sensitive magnetic resonance imaging (MRI) techniques. The distribution of SS may predict the probable underlying etiology. This study aimed to report the prevalence and natural history of superficial siderosis (SS) in a population-based study. Methods Brain MRI scans from the Mayo Clinic Study of Aging… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
30
0
2

Year Published

2018
2018
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(35 citation statements)
references
References 22 publications
3
30
0
2
Order By: Relevance
“…APOE4 carriers tend to have a greater burden of amyloid in vessels, leading to microbleeds, but APOE2 carriers appear to be more prone to such vessels rupturing and causing larger hemorrhages (Biffi et al, 2011;Charidimou et al, 2015;Yu et al, 2015). This increased propensity of APOE2 carriers to hemorrhage from CAA is also supported by a recent paper demonstrating that they are much more likely to show superficial siderosis on MRI scans (Pichler et al, 2017). The importance of beta-amyloid deposits in vessels has been highlighted recently in the replicated finding that APOE4-positive AD patients treated with anti-amyloid antibodies are at increased risk for amyloidrelated imaging abnormalities (ARIAs).…”
Section: Cerebrovascular Diseasementioning
confidence: 75%
“…APOE4 carriers tend to have a greater burden of amyloid in vessels, leading to microbleeds, but APOE2 carriers appear to be more prone to such vessels rupturing and causing larger hemorrhages (Biffi et al, 2011;Charidimou et al, 2015;Yu et al, 2015). This increased propensity of APOE2 carriers to hemorrhage from CAA is also supported by a recent paper demonstrating that they are much more likely to show superficial siderosis on MRI scans (Pichler et al, 2017). The importance of beta-amyloid deposits in vessels has been highlighted recently in the replicated finding that APOE4-positive AD patients treated with anti-amyloid antibodies are at increased risk for amyloidrelated imaging abnormalities (ARIAs).…”
Section: Cerebrovascular Diseasementioning
confidence: 75%
“…In another population-based study (n=1,412) [143] of individuals aged 50 to 89 (of which a portion had dementia or mild cognitive impairment [144]), using data from the Mayo Clinic Study of Aging, 13 subjects (0.9%) were found to have cSS. Unlike the RS, only about one-fifth of these patients had concurrent CMB, a finding which is consistent with other reports [145].…”
Section: Cortical Superficial Siderosismentioning
confidence: 99%
“…Possible causes of these bleeds include intracranial tumors, head trauma, arteriovenous malformations, aneurysms, cervical root avulsion, neurosurgical procedures, brachial plexus injury, amyloid angiopathy, and chronic subdural hematomas [6][7][8]. Hemosiderin is most commonly found surrounding the brain stem, cerebellum, and basal cisterns as it pools in the posterior fossa, although superficial cortical deposition can be seen as well [1,5,9]. The diagnostic procedure of choice is T2 and susceptibility-weighted (SW) MRI, which visualizes paramagnetic blood products as hypointense [5,9].…”
Section: Discussionmentioning
confidence: 99%
“…Superficial siderosis is a rare neurological disease associated with chronic subpial deposition of hemosiderin throughout the brain and spinal cord due to recurrent episodes of subarachnoid hemorrhage [1][2][3][4][5][6][7][8][9]. Disease prevalence within the general population remains unclear, although population-based studies have reported a range of 0.21%-1.43% in patients aged over 55 years, with greater prevalence in those aged over 69 years [2,10]. The disease presents clinically as a triad of bilateral sensorineural hearing loss, ataxia, and myelopathy with pathognomonic findings of hypointensities along the brainstem, cerebellum, and spinal cord identified by multisequence MRI.…”
Section: Introductionmentioning
confidence: 99%